1987
DOI: 10.1007/bf00385041
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in life-history traits of the bark beetle Ips calligraphus as influenced by phloem thickness

Abstract: Reproduction and development of Ips calligraphus (Germar) (Coleoptera: Scolytidae) occur primarily in the phloem (inner bark) tissue of its pine hosts. In slash pine (Pinus elliottii Engelm. var. elliottii), phloem thickness can vary widely from tree to tree. We compared adult residence time and fecundity and progeny development time, body size, and sex ratio of this beetle when reared in slash pine bolts and bark slabs with phloem thicker or thinner than average adult body width. Most studies were conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
0
21
2
Order By: Relevance
“…These results contrast with other studies that have emphasized the positive eects of phloem thickness for bark beetles (Amman 1972;Berryman 1976;Haack et al 1987aHaack et al , 1987b. Moreover, phloem quantity is expected to have a direct eect on reproduction.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…These results contrast with other studies that have emphasized the positive eects of phloem thickness for bark beetles (Amman 1972;Berryman 1976;Haack et al 1987aHaack et al , 1987b. Moreover, phloem quantity is expected to have a direct eect on reproduction.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, phloem quantity is expected to have a direct eect on reproduction. The mean thickness of phloem in our focal stand (1.07 mm, Table 1) was less than the body width of pine engravers (ca 1.45 mm), requiring beetles to also consume less nutritious outer bark and xylem (Haack et al 1987a). The lack of an eect of phloem thickness in our study cannot be attributed to greater variation in the measurement of phloem thickness for each tree (due to either intrinsic variation or measurement error), as the four measurements taken for each tree were not more variable for phloem than for MAI or BAI for the past 5 or 10 years (analyzed following Sokal and Braumann 1980;data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mountain pine beetle success has been linked to phloem thickness (Amman 1972b;Berryman 1976;Haack et al 1987). Several studies have indicated that larger-diameter trees with thicker phloem and bark produce brood beetles that are larger in size (Amman & Pace 1976;.…”
Section: Discussionmentioning
confidence: 99%
“…Thicker phloem provides mountain pine beetles with access to a larger quantity of the resource, and a higher quality food source Amman 1972b;Berryman 1976;. Reproductive fitness, measured by short larval development time, early emergence, and large quantity of offspring per parent female, was greater in Ips calligraphus (Germar) beetles developing in trees with thick phloem (Haack et al 1987). Mountain pine beetles from small trees have been shown to produce broods with a slightly different genotype, a sex ratio strongly skewed towards females, and slower development, than broods from larger trees ).…”
Section: Introductionmentioning
confidence: 99%